Analisis Penerapan Kebijakan Rekam Medis Elektronik (RME) terhadap Efektivitas Pelayanan Kesehatan di Puskesmas Koto Lolo Kota Sungai Penuh Tahun 2025 (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
One of the technologies used to improve the quality of healthcare services at Community Health Centers (Puskesmas) is the implementation of Electronic Medical Records (EMR). This study aimed to analyze the effect of Electronic Medical Record (EMR) policy implementation on the effectiveness of healthcare services at Koto Lolo Community Health Center, Sungai Penuh City, in 2025. This study employed a quantitative research design with a cross-sectional approach. The sample consisted of 84 respondents selected using a total sampling technique. Data were collected through observations, interviews, and questionnaires and were analyzed using statistical tests. The results showed a significant relationship between the implementation of Electronic Medical Record (EMR) policies and the effectiveness of healthcare services (p = 0.003). These findings indicate that EMR implementation can enhance service effectiveness through faster, more accurate, and integrated health information management. However, this study was limited to a single healthcare facility, which restricts the generalizability of the findings. Therefore, future studies are recommended to include a larger number of healthcare facilities and examine additional factors that may influence the successful implementation of EMR systems.